(untitled) (Journal of Engineering, 2014)
This research presents the kinetics of the saponification reaction using mixed fats of olein and stearin [in the ratio (3:1)] with NaOH solution. In this reaction, excess solution of NaOH was used to ensure the reaction being irreversible. Three parameters were varied to show their effects on the reaction rate .They are: percentage excess of NaOH solution (10 % - 100 %) , temperature (100-150)oC , and stirring speed (400-1100) rpm. It was noticed that increasing the percentage excess of NaOH solution enhances the rate of reaction while increasing temperature decreases the reaction rate since it is exothermic reaction. Increasing stirring speed also improves the reaction rate because it is mass transfer controlled .Calculations of the activation energy and the frequency factor was also performed. A new mathematical model for calculation of the reaction – rate constant was derived. It is shown that a good approximation was obtained between the experimental and calculated values of the reaction – rate constant k .